Fresh Moringa Stenopetala leaves consumption and its determinants among pregnant women in southern Ethiopia - Derbo, Zeritu Dewana; Debelew, Gurmesa Tura (Frontiers in Nutrition, 2024)
Background A woman’s health and nutritional status has significant impact on her pregnancy situation. However, many pregnant women are undernourished. Moringa stenopetala is a plant consumed worldwide in various forms, and its consumption showed a reduction in the incidence of malnutrition. Although Moringa stenopetala is rich in essential macro- and micronutrients, there is little evidence on the proportion and determinants of fresh Moringa stenopetala leaf intake among pregnant women. The objective of this study was to fill this gap in the littérature and provide a baseline evidence for further research or intervention by investigation the proportion and determinants of fresh Moringa stenopetala leaf intake among pregnant women in the Gamo zone, south Ethiopian region. Methods A community-based cross-sectional study was conducted among 623 randomly selected pregnant women using a pre-tested and structured questionnaire via a face-to-face interview. The consumption pattern was assessed based on a self-reported dietary history over the last 30 days before data collection. Multivariable logistic regression model was fitted using STATA version 14. An adjusted odds ratio with a 95% confidence interval was reported to show an association between the dependent and independent variables with level of statistical significance at a p-value of <0.05. Results The proportion of fresh Moringa stenopetala leaves intake among pregnant women was 49.60% (95% CI: 45.67, 53.52%). The déterminants of fresh moringa leaf intake were being below 24 years old (AOR: 2.92; 95% CI: 1.51, 5.63), rural résidence (AOR: 1.97; 95% CI: 1.10, 3.50), antenatal care attendance (AOR: 2.08; 95% CI: 1.03, 4.21), history of contraceptive use (AOR: 1.88; 95% CI: 1.03, 3.55), and having a good knowledge about the importance of moringa Stenopetala (AOR: 9.76; 95% CI: 5.30, 17.95). Conclusion The study showed that almost half of the pregnant women consumed fresh Moringa stenopetala leaves. Women’s age, place of residence, prenatal care, history of contraceptive use, and knowledge of the benefits of Moringa Stenopetala were positively associated with the consumption of fresh Moringa Stenopetala leaves. Therefore, health authorities and stakeholders involved in maternal and child health need to target older women, and urban residents and promote the benefits of consumption by strengthening uptake of maternal health services and raising awareness about Moringa Stenopetela. Future studies involving large scale and longitudinal designs evidence are required to further validate the findings so that this nutritious diet can be promoted widely among pregnant women in the study area and Ethiopia at large.